Peran TikTok sebagai Alat Digital Marketing dalam Meningkatkan Stream Count dan Pendapatan Musisi: (Studi Kasus: Viralisasi Lagu "Mangu" oleh Fourtwnty) - Muhammad Ilham Topik Hidayat; Suryanto Suryanto (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study aims to analyze the role of TikTok as a digital marketing tool in increasing the number of streams and musicians' income, with a case study of the viralization of the song "Mangu" by Fourtwnty. Using a qualitative approach with a case study method, this study explores the dynamics of the virality of music content on the TikTok platform and its impact on the digital music ecosystem. The results show that the virality of songs is not solely triggered by algorithms, but also by the power of emotional narratives, the relevance of lyrics to the user experience, and the active participation of the audience in the form of production. This phenomenon is driving cross-platform conversions, where TikTok users are switching to streaming services such as Spotify and YouTube, thereby increasing digital royalties and opening up live performance opportunities for musicians. Organic marketing strategies based on audience engagement have proven to be effective in creating broad and sustainable exposure, especially among the digital native generation. This research confirms that TikTok is not only an entertainment platform, but also a strategic medium in building music branding and monetizing works creatively. These findings provide important implications for independent musicians and the music industry in designing adaptive and participatory promotional strategies in an increasingly competitive digital economy.